Perancangan Aplikasi Sistem Pakar Penyakit Roseola Dengan Menggunakan Metode Certainty Factor - Lola Fida Putri (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
Measles Roseola usually attacks infants with transmission from a sprinkling of sufferers' saliva. Roseola must be treated quickly because it can cause liver and brain inflammation. Roseola's disease for people whose economy is low is not given much attention because it is often diagnosed in severe or acute illness. This is because the red rash in infants is a common measles. Early diagnosis of Roseola's disease is a good way to avoid adverse consequences for the baby's health. The Roseola disease expert system is able to help low-income people to self-diagnose the disease. Roseola's disease expert system is applied knowledge gained from experts, namely specialist dermatologists in children. Processing of symptoms based on facts with the value and calculation of the Certainty Factor method. Certainty Factor determines good results by combining expert values and user values.